Respuesta :
I hope this helps you
f (144)= square root of 144+12=12+12=24
g (144)=2.square root of144=2.12=24
(f-g)(144)=24-24=0
f (144)= square root of 144+12=12+12=24
g (144)=2.square root of144=2.12=24
(f-g)(144)=24-24=0
we have
[tex]f(x)=\sqrt{x}+12[/tex]
[tex]g(x)=2\sqrt{x}[/tex]
we know that
[tex](f-g)(144)=f(144)-g(144)[/tex] -------> equation A
Step 1
Find the value of [tex]f(144)[/tex]
For [tex]x=144[/tex]
substitute in f(x)
[tex]f(144)=\sqrt{144}+12[/tex]
[tex]f(144)=12+12[/tex]
[tex]f(144)=24[/tex]
Step 2
Find the value of [tex]g(144)[/tex]
For [tex]x=144[/tex]
substitute in g(x)
[tex]g(144)=2\sqrt{144}[/tex]
[tex]g(144)=2(12)[/tex]
[tex]g(144)=24[/tex]
Step 3
Find [tex](f-g)(144)[/tex]
Substitute the values in the equation A
[tex]24-24=0[/tex]
therefore
the answer is the option
[tex]0[/tex]